ANALISIS IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH PENGGERAK JENJANG SD - Zakia Arafat, Litsa; Puji Rahayu, Ayu; Amalia, Ana; Asiah, Siti; Latifah, Siti; Yulia, Rini; Ahmad Saepurohman, Aam; Yeni Juarsih, Neng (CV. Kalimasada Group, 2025)
This research was conducted to gain knowledge and conduct a review of the implementation and analysis of the implementation of the Merseka Curriculum in Driving Schools, namely SDN 2 Cibunar and SDN 3 Kersamenak in Garut Regency. This research was conducted using a qualitative descriptive approach where data was collected by interviews, observation and documentation. The informants in this research were school principals, teachers, students and parents. To ensure the validity of the data, time was extended in collecting data, observing activities in the two elementary schools studied, and triangulating the data. The results of the research found that the Merdeka Curriculum must be implemented in Driving Schools, where in its implementation there are differences in stage achievements between SDN 2 Cibunar and SDN 3 Kersamenak